Epic in Republican Rome. - Goldberg, Sander M. (Oxford University Press, 1995)
This book is a major new study of the epic poetry of Republican Rome. Goldberg treats the creators of these now-fragmentary works not simply as predecessors of Vergil, but as pioneers and poets in their own right. But Goldberg goes beyond practical criticism, exploring in the literary experiments of Andronicus, Naevius, Ennius, and Cicero issues of poetry and patronage, cultural assimilation and national ideology, modeling and originality that both come to characterize Roman literature of all periods and continue to shape modern responses to that literature. What emerges from Goldberg's study.